Incremental value of the combined brain-cardiac CT protocol on prediction of atrial fibrillation after stroke. (March 2023) - Braillon, Alexandra; Bernard, Angélique; Leclercq, Thibault; Duloquin, Gauthier; Pommier, Thibaut; Benali, Karim; Comby, Pierre-Olivier; Loffroy, Romaric; Midulla, Marco; Ricolfi, Frédéric; Béjot, Yannick; Guenancia, Charles
Introduction: Atrial fibrillation (AF) is one of the most common causes of ischemic stroke. It is essential to target patients at highest risk of AF detected after stroke (AFDAS), who should benefit from a prolonged rhythm screening strategy. Cardiac-CT angiography (CCTA) was added to the stroke protocol used in our institution in 2018. We sought to assess, for AFDAS, the predictive value of atrial cardiopathy markers by a CCTA performed on admission for acute ischemic stroke. Patients and Methods: From November 2018 to October 2019, consecutive stroke patients with no history of AF were included. Let atrial volume (LAV), epicardial adipose tissue (EAT) attenuation and volume, and LAA characteristics were measured on CCTA. The primary endpoint was the presence of AFDAS at follow-up, diagnosed by continuous electrocardiographic monitoring, long-term external Holter monitoring during hospital stay, or implantable cardiac monitor (ICM). Results: Sixty of the 247 included patients developed AFDAS. Multivariable analysis shows independent predictors of AFDAS: age >80 years (HR 2.46; 95%CI (1.23–4.92), p  = 0.011), indexed LAV >45 mL/m 2 (HR 2.58; 95%CI (1.19–5.62), p  = 0.017), EAT attenuation > −85HU (HR 2.16; 95%CI (1.13–4.15), p  = 0.021) and LAA thrombus (HR 2.50; 95%CI (1.06–5.93), p  = 0.037). Added consecutively to AFDAS prediction AS5F score (combining age and NIHSS >5), these markers had an incrementally better predictive value compared with the global Chi 2 of the initial model ( p  = 0.001, 0.035, and 0.015 respectively). Discussion and conclusion: Adding CCTA to the acute stroke protocol to assess markers of atrial cardiopathy associated with AFDAS may help to better stratify the AF screening strategy, including the use of an ICM. Graphical abstract